Performative challenges of multimedia composition for saxophone: case studies in works by Mark Oliveiro and Ted Moore - Sousa, Jorge (2024)
Technology is omnipresent, conditioning our daily expe- riences and inherently interfering in the artistic creation and performances ongoing in the contemporary world. Embracing technology and incorporating it into art lies at the basis of concepts such as the post-digital, which contemplates criticism and attention towards the digital culture that surrounds us, revealing and reflecting on its sociocultural effects. Artistic creation for saxophone, elec- tronics, and visual features represents a reality within the contemporary compositional scenario. As a result of the idiosyncrasies of this compositional aesthetic, performers face particular performative challenges. Aiming to identify the key performative challenges embedded in the perfor- mance, we here explore two works for tenor saxo- phone, electronics and visual features - Black(midi)matter (for ten- or saxophone and multimedia) by Mark Oliveiro, and sac- cades (for tenor saxophone, electronics, tape and video) by Ted Moore. Therefore, the case study methodological approach is applied to each work and spanning the perfor- mative experience, a literature review, and contact with the composers. Technical, technological, and aesthetic chal- lenges confront performers, demanding the expansion of their learning into additional areas. This includes specific skills regarding music technology, controlling body move- ments, physical awareness of the performance space and the developing strategies with the aim of establishing an artistic symbiosis between the technology and the per- former through sound and musical expression. Addition- ally, it is essential that the performers complete solid and specialized training in the instrument, from both an aca- demic and artistic perspective, encompassing a meticu- lous mastery of extended techniques, enabling an enriched and contextually informed musical performance.